2021
DOI: 10.3390/cancers13102296
|View full text |Cite
|
Sign up to set email alerts
|

The Role of p53 Dysfunction in Colorectal Cancer and Its Implication for Therapy

Abstract: Colorectal cancer (CRC) is one of the most common and fatal cancers worldwide. The carcinogenesis of CRC is based on a stepwise accumulation of mutations, leading either to an activation of oncogenes or a deactivation of suppressor genes. The loss of genetic stability triggers activation of proto-oncogenes (e.g., KRAS) and inactivation of tumor suppression genes, namely TP53 and APC, which together drive the transition from adenoma to adenocarcinoma. On the one hand, p53 mutations confer resistance to classica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 195 publications
(230 reference statements)
4
30
1
Order By: Relevance
“…Among the 10 genes, we found that 8 genes had SNPs in LGD and HGD. The associations of 5 of these genes ( TP53 , 14 KRAS , 15 GSTP1 , 16 MTHFR , 17 and ABCC2 18 ) with colonic adenoma have previously been reported in several studies, whereas no such association of XRCC1, UMPS , or DPYD has been reported to date ( Supplementary Table 1 ). In addition, we selected XRCC1 as the focus of this study given previous results from a meta-analysis demonstrating a relationship between the XRCC1 rs25487 polymorphism and sensitivity to platinum-based chemotherapy drugs in CRC patients.…”
Section: Resultsmentioning
confidence: 95%
“…Among the 10 genes, we found that 8 genes had SNPs in LGD and HGD. The associations of 5 of these genes ( TP53 , 14 KRAS , 15 GSTP1 , 16 MTHFR , 17 and ABCC2 18 ) with colonic adenoma have previously been reported in several studies, whereas no such association of XRCC1, UMPS , or DPYD has been reported to date ( Supplementary Table 1 ). In addition, we selected XRCC1 as the focus of this study given previous results from a meta-analysis demonstrating a relationship between the XRCC1 rs25487 polymorphism and sensitivity to platinum-based chemotherapy drugs in CRC patients.…”
Section: Resultsmentioning
confidence: 95%
“…In addition to KRAS and PIK3CA mutations, CRC cells used in this study harbored mutations in TP53. Preclinical studies suggested that there are correlations between resistant to therapies and TP53 alterations in mCRC [40][41][42] . Our results showed that liver ECs induced HER3-AKT activation and cell survival in all cell lines we used, which harbor either wild-type or mutant TP53.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of genomic instability and the successive mutations in genes such as KRAS and SMADs trigger the formation of dysplastic tubular adenomas [ 61 , 74 , 75 ]. As a result, alterations in the Transforming growth factor-β (TGF-β) pathway and the inactivation of the TP53 gene culminate in the formation of invasive adenocarcinomas [ 61 , 75 , 76 , 77 ]. Once epithelial tumor tissue is in constant interaction with cells in tumor microenvironment (TME) through the action of cytokines, chemokines, and growth factors, additional mutations, and changes in TME components give advantage to tumor clones and allow the tumors to later metastasize to distant organs [ 78 , 79 , 80 , 81 , 82 ] ( Figure 2 ).…”
Section: The Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%